Pedobarographic and Radiological Analysis After Treating a Talus Neck Fracture - TİMURTAŞ, EREN; POLAT, MİNE GÜLDEN; KURU ÇOLAK, TUĞBA (ELSEVIER SCIENCE INC, 2016)
Misalignment of the talar neck after surgical repair can redistribute the load among the posterior, middle, and anterior facets of the subtalar joints, which can change the joint biomechanics, cause arthritis, and impair function. However, we found no studies analyzing the plantar pressures after treatment of talus neck fracture. We determined the dynamic plantar pedobarographic and radiographic characteristics and ankle range of motion, function, and pain among patients after surgical repair of talar neck fractures. A total of 19 patients completed the assessments. The median follow-up period was 29 (range 12 to 113) months. At the last visit, the mean pain score was 3.3 on a 10-cm visual analog scale. The mean American Orthopaedic Foot and Ankle Society function scale score was fair (73.5), and the mean range of motion was restricted in 4 planes. The mean maximum force was lower in the hindfoot (p = .002) and midfoot (p = .03) of the injured foot than in the noninjured foot. The mean peak pressure was lower in the hindfoot (p = .05) but higher in the forefoot (p = .03). Radiographic measurements revealed differences between the feet in the talo-first metatarsal angle (p = .002), Meary's angle (p = .001), and the medial cuneiform-fifth metatarsal angle (p = .002). Radiographic and pedobarographic analysis showed an elevated arch in the injured foot. Thus, talar injury and immobilization can affect the stance and the gait cycle in these patients. Pain, range of motion, function, and the weight transfer pattern should be evaluated carefully during the follow-up period to provide the best postoperative results. (C) 2016 by the American College of Foot and Ankle Surgeons. All rights reserved.
Keywords: foot; fracture; injury; pedobarography; talus; DISPLACED TALAR NECK; BODY FRACTURES; HINDFOOT; MALALIGNMENT; FIXATION; MIDFOOT; GAIT